The Role of Digital Technology as A Medium for Islamic Counselling to Enhance Anonymous Self-Disclosure: A Platform Study of Arahcelah - Thohir, Mohamad; Adhilah, Fizna; Hotim, Hotim; Wibisono, Putra (Jurusan Bimbingan dan Konseling Islam, 2023)
In the era of Society 5.0, digital technology provides users with the opportunity to communicate and express themselves in unique ways. Some users choose to reveal their real identities, while others opt for anonymity to ensure security and confidentiality. This can be advantageous for the development of counselling media, as it can assist counselees in self-disclosure with ease and comfort. Arahcelah is a counselling medium developed to enhance client self-disclosure through an anonymous process. The purpose of this study is to determine the role of the Arahcelah platform in the era of digital technology as a counselling medium in improving anonymous self-disclosure. The research method used is descriptive qualitative analysis of the counselling service process on the Arahcelah platform. This research demonstrates that Arahcelah can be an effective counselling medium, enhancing individual self-disclosure through five key roles: practicality, openness, confidentiality, empathy, and responsiveness. These roles align with Islamic values.